Neuromuscular fitness in early life and its impact on bone health in adulthood: a systematic review - Lopes Barbosa, Cynthia Correa; Possamai Romanzini, Catiana Leila; Batista, Mariana Biagi; Fernandes, Romulo Araujo [UNESP]; Romanzini, Marcelo; Kemper, Han; Coelho-e-Silva, Manuel Joao; Vaz Ronque, Enio Ricardo (Soc Pediatria Sao Paulo, 2020)
Objective: To systematically review the literature to verify the relationship between neuromuscular fitness indicators in childhood/adolescence and bone strength variables in adulthood. Data sources: A systematic review was conducted in PUBMED, SCOPUS, SPORTDiscus, Web of Science, PsycINFO, LILACS, and SciELO, covering the entire period until March 2019. Data synthesis: The search identified 1149 studies. After duplicity analysis and eligibility criteria, four studies were reported. In one study, baseline was childhood and, in the others, adolescence. In childhood, when adjusting the model for age and body mass index, a statistically significant relation was found for girls: standing long jump with quantitative ultrasound index (beta=0.11; p<0.05) and with speed of sound (beta=0.14; p<0.01). However, when controlling muscular performance in adulthood, the relationship was no longer significant. In adolescence, coefficients ranged from 0.16 for neuromotor battery and bone mineral density (BMD) in the lumbar region to 0.38 for hanging leg lift test and BMD of arms. The explained variance varied between 2% (bent arm hang for BMD total) and 12% (hanging leg-lift for BMD arms), therefore, a higher performance in neuromuscular fitness in adolescence was associated with better bone strength in adulthood. Conclusions: In adults, bone strength variables showed significant correlation from low to moderate magnitude with neuromuscular fitness indicators in adolescence, but not in childhood, after controlling for adult performance in neuromuscular fitness. However, there is limited evidence to support the neuromuscular fitness in early life as a determinant of bone strength in adulthood.
Keywords: Muscle strength; Bone mineral density; Childhood; Adolescence